Response characteristics of the orthogonal antennas of electromagnetic azimuthal resistivity measurement while drilling (MWD) tool for coal mining - Gang CHEN (Meitian dizhi yu kantan)
Objective and Methods This study aims to determine the factors influencing the detection performance of the electromagnetic azimuthal resistivity measurement while drilling (MWD) tool for coal mining in horizontal wells. Through finite element numerical simulations, this study conducted boundary detection using orthogonal coupling coils with multiple frequencies and coil pitches. This allowed for determining the optimal asymmetric arrangement of coils, as well as the optimal working parameters of frequency, source-detector separation distance, and coil pitch suitable for high-resistivity coal seams. Results and Conclusions The comparative study of orthogonal and inclined coils reveals that in the case of directional signals of inclined coils, although the amplitude ratio signals were theoretically enhanced with an increase in the coil pitch, the actual amplitude of induced electromotive force in inclined coils decreased. This complicates signal acquisition. This study designed an orthogonal coil array structure for electromagnetic azimuthal resistivity measurement for coal mines, enabling concurrent resistivity and interface detection for high-resistivity coal seams. Furthermore, this study obtained the optimized parameters of frequency, source-detector separation distance, and coil pitch for mining of these coal seams. The results of this study provide a basis for electromagnetic azimuthal detection along coal seams in wells in underground coal mines.